Therapy for Duchenne muscular dystrophy: renewed optimism from genetic approaches. - Fairclough, R; Wood, M; Davies, K (2013)
Duchenne muscular dystrophy (DMD) is a devastating progressive disease for which there is currently no effective treatment except palliative therapy. There are several promising genetic approaches, including viral delivery of the missing dystrophin gene, read-through of translation stop codons, exon skipping to restore the reading frame and increased expression of the compensatory utrophin gene. The lessons learned from these approaches will be applicable to many other disorders.